2022
DOI: 10.3389/fmolb.2022.1055823
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazine bioorthogonal chemistry derived in vivo imaging

Abstract: Bioorthogonal chemistry represents plenty of highly efficient and biocompatible reactions that proceed selectively and rapidly in biological situations without unexpected side reactions towards miscellaneous endogenous functional groups. Arise from the strict demands of physiological reactions, bioorthogonal chemical reactions are natively selective transformations that are rarely found in biological environments. Bioorthogonal chemistry has long been applied to tracking and real-time imaging of biomolecules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The increases in R1 relaxation in vivo were consistent with the ex vivo Gd concentrations measured by inductively coupled plasma mass spectrometry (ICP-MS), 58 suggesting the in vivo imaging results are reliable. In 2022, Lin and Gao's group adopted a similar bio-orthogonal strategy with tetra-acetylated N-azidoacetylgalactosamine (Ac 4 ManAz) to investigate whether 19 F MRI is feasible for in vivo imaging. 59 Through intratumoral injection of the bioorthogonal pair (Ac 4 ManAz/DBCO-19 F) into xenografted tumors, they showed that in vivo bioorthogonal 19 F-MRI could be feasible (Figure 6).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…The increases in R1 relaxation in vivo were consistent with the ex vivo Gd concentrations measured by inductively coupled plasma mass spectrometry (ICP-MS), 58 suggesting the in vivo imaging results are reliable. In 2022, Lin and Gao's group adopted a similar bio-orthogonal strategy with tetra-acetylated N-azidoacetylgalactosamine (Ac 4 ManAz) to investigate whether 19 F MRI is feasible for in vivo imaging. 59 Through intratumoral injection of the bioorthogonal pair (Ac 4 ManAz/DBCO-19 F) into xenografted tumors, they showed that in vivo bioorthogonal 19 F-MRI could be feasible (Figure 6).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…In 2022, Lin and Gao's group adopted a similar bio-orthogonal strategy with tetra-acetylated N-azidoacetylgalactosamine (Ac 4 ManAz) to investigate whether 19 F MRI is feasible for in vivo imaging. 59 Through intratumoral injection of the bioorthogonal pair (Ac 4 ManAz/DBCO-19 F) into xenografted tumors, they showed that in vivo bioorthogonal 19 F-MRI could be feasible (Figure 6). For validation, they used tris(2carboxyethyl) phosphine (TCEP), a chemical that can reduce the azido in Ac 4 ManAz to an amine, to abolish the bio- orthogonal reaction.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…1). [10][11][12] Key reactions of bioorthogonal chemistry include Staudinger ligation or native chemical ligation, strain-promoted [3 + 2] azide-alkyne and alkyne-nitrone cycloaddition (SPAAC and SPANC) reaction, dienophile and tetrazine inverse electrondemand Diels-Alder (IEDDA) ligation, oxime, and hydrazone ligations along with photoinducible bioorthogonal reactions. 4,13 As such, the IEDDA ligation techniques are quite promising and have been applied in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 For instance, combinations of tetrazines tethered to fluorescent probes and alkene-derivatized bio-molecules�or vice versa�allowed in vivo imaging studies of tumor sites. 12 Metal complexes of tetrazines have been known for a long time. 13 In this respect, the tetrazine nitrogen atoms are rather poor Lewis bases, requiring assistance from another coordinating unit to obtain a good chelating ligand, most commonly a 2pyridyl substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, isocyanides react via a [4 + 1] cycloaddition with 1,2,4,5-tetrazines, affording an iminopyrazole. Investigations on the reactivity of tetrazines gained momentum in recent years, regarding the use of the tetrazine/alkene and tetrazine/isocyanide ligation in aqueous solution as a bioorthogonal tool. , For instance, combinations of tetrazines tethered to fluorescent probes and alkene-derivatized biomoleculesor vice versa allowed in vivo imaging studies of tumor sites …”
Section: Introductionmentioning
confidence: 99%